SUBURBAN PASSENGER SERVICES - INTERNATIONAL SOCIAL AND ECONOMIC COOPERATION OF RUSSIA AND UKRAINE - Yakymchuk, S. V. (Science and Transport Progress, 2007)
As the example of collaboration of Russia and Ukraine in suburban transportations an electric train is considered the «Prince Vladimir» by the report of Belgorod–Kharkov.